2018
DOI: 10.3390/nu10111816
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Mononuclear Cell Metabolism Acutely Adapted to Postprandial Transition and Mainly Reflected Metabolic Adipose Tissue Adaptations to a High-Fat Diet in Minipigs

Abstract: Although peripheral blood mononuclear cells (PBMCs) are widely used as a valuable tool able to provide biomarkers of health and diseases, little is known about PBMC functional (biochemistry-based) metabolism, particularly following short-term nutritional challenges. In the present study, the metabolic capacity of minipig PBMCs to respond to nutritional challenges was explored at the biochemical and molecular levels. The changes observed in enzyme activities following a control test meal revealed that PBMC meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…This goal is achieved by combining an imaging platform based on CT evaluation of AT distribution, weight evolution, food intake with changes in circulating lipidome and metabolome, with a view of specific transcripts in the subcutaneous AT and in the transcriptome of the peripheral blood mononuclear cells (PBMCs). These later were chosen as they may share, at least partially, share the expression profile of different sets of genes with other tissues, including those that reflect metabolic responses [14][15][16]. Furthermore, the lipidomic changes were validated in a cohort of human subjects to confirm the robustness of these observations.…”
Section: Introductionmentioning
confidence: 99%
“…This goal is achieved by combining an imaging platform based on CT evaluation of AT distribution, weight evolution, food intake with changes in circulating lipidome and metabolome, with a view of specific transcripts in the subcutaneous AT and in the transcriptome of the peripheral blood mononuclear cells (PBMCs). These later were chosen as they may share, at least partially, share the expression profile of different sets of genes with other tissues, including those that reflect metabolic responses [14][15][16]. Furthermore, the lipidomic changes were validated in a cohort of human subjects to confirm the robustness of these observations.…”
Section: Introductionmentioning
confidence: 99%
“…After two months of HFHS feeding the mini-pigs developed an obesity and insulin resistance-like phenotype, with a significant increase in HOMA-IR index (from 0.075 ± 0.03 to 0.41 ± 0.08) and body weight (from 31.5 ± 1.4 kg to 44.7 ± 1.7 kg), most likely as the consequence of fat deposition in the visceral and subcutaneous adipose tissue [ 3 ]. More details about biochemical and clinical phenotyping were published previously [ 5 , 6 ]. The current study is exclusively based on the analyses of the postprandial response.…”
Section: Resultsmentioning
confidence: 99%
“…It is as yet unclear at which stage during overfeeding these adaptive processes can be regarded as part of normal metabolic flexibility or whether they reflects negative side effects in the spectrum of the metabolic syndrome [ 2 ]. Thus, we have recently shown that in mini-pigs overfed with a high fat–high sucrose (HFHS) diet for two months, major modifications in the postprandial metabolism occur after only one week of feeding [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, statin use is frequently associated with myalgia leading to non-compliance with the recommended treatment protocol. To better understand the mechanisms underlying SAM, we assessed mitochondrial parameters and the abundance of superoxide in Simvastatin users, and matched controls, using platelets and PBMCs as a surrogate model for skeletal muscle [28][29][30][31][32][33] .…”
Section: Discussionmentioning
confidence: 99%
“…We used blood cells in this study because it is less invasive to access compared to muscle cells obtained from muscle biopsies. Moreover PMBCs and platelets are well-characterized surrogate models for assessing pharmacological effects on skeletal muscle mitochondrial function [28][29][30][31][32][33] . In addition to increasing mitochondrial respiration, we observed that Simvastatin increases production of mitochondrial superoxide, a representative reactive oxygen species (ROS) by-product of mitochondrial respiration, and that patient-reported myalgia increases with increasing abundance of superoxide, but does not trend with oxygen consumption rate (OCR) in mitochondria from patient-derived peripheral blood cells.…”
mentioning
confidence: 99%